Pengaruh Konsentrasi AB Mix terhadap Pertumbuhan dan Hasil Sawi Pakcoy (Brassica Rapa L.) Secara Hidroponik Sistem Rakit Apung - Sipayung, Patricius; Tarigan, Rio Stepanus; Pinem, Ricky Tampe Tuahta (LPPM Universitas Katolik Santo Thomas Medan, 2025)
This research aims to determine the effect of AB MIX concentration on the growth and yield of Pakcoy mustard greens (Brassica rapa L.) using a hydroponic floating raft system. This research also aims to see the growth response of Pak Choy mustard greens to the AB Mix nutrient concentration given and find out which concentration is best for the growth and production of Pak Choy mustard greens using a hydroponic floating raft system. The pak choy plant (Brassica rapa L.) or what is also commonly called spoon mustard greens is a type of leaf vegetable that is classified as mustard greens. Pakcoy is currently one of the favorite vegetables in Indonesia besides mustard greens and lettuce. This plant is used by the community, especially traders, for various kinds of food preparations and also as decoration. Pakcoy plants have thick leaf bones so they are crunchy when consumed. This research used a non-factorial Completely Randomized Design (CRD) with 1 factor studied, namely the nutritional effect of AB Mix, which consisted of 4 treatment levels, namely A0 = without AB Mix, A1 = 35 ml AB Mix/9 liters of water, A2 = 40 ml AB Mix/9 liters of water and K3 = 45 ml AB Mix/9 liters of water. The parameters observed in this study consisted of plant height, number of leaves, root length, wet weight per plant (sample), plant wet weight per plot, root wet weight, root dry weight (oven).